2013
DOI: 10.1093/ndt/gft259
|View full text |Cite
|
Sign up to set email alerts
|

Underweight, overweight and obesity in paediatric dialysis and renal transplant patients

Abstract: Overweight and obesity, rather than underweight, are highly prevalent in European children on RRT. Short stature among graft recipients had a strong association with overweight, while underweight appears to be only a problem in infants. Our findings suggest that nutritional management in children receiving RRT should focus as much on the prevention and treatment of overweight as on preventing malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 34 publications
(68 reference statements)
3
33
0
2
Order By: Relevance
“…Protein energy wasting in children in the United States with chronic renal insufficiency ranges from 7% to 20% . Recent examinations of two large databases found that 6% and 10% of patients beginning renal replacement therapy were underweight in Europe and the United States, respectively . Children on maintenance dialysis for <1 year were more likely to be underweight than were those who spent 1–3 years on dialysis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein energy wasting in children in the United States with chronic renal insufficiency ranges from 7% to 20% . Recent examinations of two large databases found that 6% and 10% of patients beginning renal replacement therapy were underweight in Europe and the United States, respectively . Children on maintenance dialysis for <1 year were more likely to be underweight than were those who spent 1–3 years on dialysis .…”
Section: Discussionmentioning
confidence: 99%
“…Recent examinations of two large databases found that 6% and 10% of patients beginning renal replacement therapy were underweight in Europe and the United States, respectively . Children on maintenance dialysis for <1 year were more likely to be underweight than were those who spent 1–3 years on dialysis . Thus, a small but important proportion of children with chronic kidney disease and ESRD appear to be undernourished, and this may have important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a combination of poor appetite and decreased height or BMI led to interventions such has high calorie foods or supplements, appetite stimulants or tube feedings. Overweight and obesity are not uncommon in patients with CKD [19] with 34% of patients from the CKiD cohort having BMI above the 85 th percentile for age and gender at their first visit. We could speculate that some patients with good appetites may have been trying to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…Height values were normalized to standard deviation scores (SDS) for chronological age, according to recent national growth charts or growth charts for Northern or Southern European countries [18]. Body mass index (BMI) was calculated as weight/height 2 and expressed according to chronological age (0-1 years) or heightage (≥2 years) [19]. Reference charts from the World Health Organization were used to calculate SDS values for BMI [20,21].…”
Section: Definition Of Variablesmentioning
confidence: 99%